1986
DOI: 10.1002/jez.1402370309
|View full text |Cite
|
Sign up to set email alerts
|

Capacitated, acrosome reacted but immotile sperm, when microinjected under the mouse zona pellucida, will not fertilize the oocyte

Abstract: We have devised a procedure for mechanically inserting intact, acrosome reacted spermatozoa under the mouse zona pellucida, and have examined the ability of sperm so inserted to fertilize the mouse oocyte. Sperm immobilized by a variety of different methods are unable to fertilize the egg, despite the fact that electron microscopy confirms that they are acrosome reacted. Control experiments show that the oocytes are capable of being fertilized by motile sperm after the microinjection procedure, and that the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Direct microinjection of spermatozoa or sperm nuclei into the cytoplasm of mouse oocytes (Uehara & Yanagimachi, 1976;Thadani, 1982;Markert, 1983) was associated with an unacceptably high rate of damage to the oocytes. Subzonal injection of spermatozoa has also been reported (Metka et al, 1985;Barg et al, 1986;Lassalle et ai, 1987). The disadvantages associated with this technique include the artificial selection of an individual spermatozoon, the time-consuming skills required for the technique, the low fertilization rate and questions relating to the karyotypic normality of the resulting embryos.…”
Section: Introductionmentioning
confidence: 94%
“…Direct microinjection of spermatozoa or sperm nuclei into the cytoplasm of mouse oocytes (Uehara & Yanagimachi, 1976;Thadani, 1982;Markert, 1983) was associated with an unacceptably high rate of damage to the oocytes. Subzonal injection of spermatozoa has also been reported (Metka et al, 1985;Barg et al, 1986;Lassalle et ai, 1987). The disadvantages associated with this technique include the artificial selection of an individual spermatozoon, the time-consuming skills required for the technique, the low fertilization rate and questions relating to the karyotypic normality of the resulting embryos.…”
Section: Introductionmentioning
confidence: 94%
“…They were incubated at 37.5°C under 5% C02 in air for 2 h to allow capacitation and acrosome reaction. The incidence of acrosome reaction in similar conditions was reported to be 20-30% (Barg et al, 1986). Insemination was carried on at 37.5°C by adding 5-10 µ of preincubated sperm suspension to 100 µ M16 containing zona-free hamster oocytes (final concentration of spermatozoa was approximately 1-2 x 10 spermatozoa ml~) .…”
Section: Preparation Of Mouse Spermatozoa and Fertilization In Vitromentioning
confidence: 99%
“…Different biochemical compounds were used to induce the acrosome reaction: 1) After 1 hour of incubation in T6, spermatozoa were further incubated for 60 min in T6 containing 20 pM of A23187 (Sigma Chemical Co. St. Louis, MO) (Barg et al, 1986). 2) Spermatozoa incubated in T6 for 60, 90, or 120 rnin were further incubated in a medium containing 12 mM dbcGMP and 10 mM imidazole (Sigma Chemical Co., St. Louis, MO) for 30 min at 37°C (Talansky et al, 1987).…”
Section: Induction Of the Acrosome Reactionmentioning
confidence: 99%
“…In the mouse, moreover, a n acrosome-free but immotile spermatozoon cannot achieve fertilization after injection into the perivitelline space of a n oocyte (Barg et al, 1986). Mann (1988), however, has demonstrated that after the subzonal injection of a single motile mouse spermatozoon, fertilization and development to term can be achieved.…”
Section: Introductionmentioning
confidence: 99%